Chemical composition, aerobic stability and fermentation pattern of tomato pomace and pumpkin waste silage using fibrolytic enzymes and lactic acid bacteria - Esmaeil Ganji Jamehshooran; Kaveh Jafari khorshidi; Javad Bayat Kouhsar (International Journal of Recycling of Organic Waste in Agriculture)
Purpose This study aimed to evaluate the effect of different additives on chemical composition, fermentation characteristics, and gas production parameters of tomato pomace and pumpkin waste silages.Method Treatments were: tomato pomace silage, pumpkin waste silage, tomato pomace and pumpkin waste silage mix (50:50), tomato pomace and pumpkin waste silage mix treated with the fibrinolytic enzyme (E), tomato pomace and pumpkin waste silage mix treated with LAB made inoculants (LMI), and tomato pomace and pumpkin waste silage mix treated with E+ LMI. Representatives of samples were packed manually into laboratory silos and allowed to ensile for 1, 3, 7, 21, 45, and 90 days.Results The results showed a significant difference between the experimental treatments in chemical composition (p<0.05). The treatment of pumpkin waste showed the lowest amount of dry matter (DM), insoluble fibers in neutral detergent (NDF), and insoluble fibers in acidic detergent (ADF). The value of crude protein (CP) showed a decreasing trend with increasing time after ensiling. The treatment with bacterial and enzymatic additives had a faster drop in pH and a lower final pH compared to other treatments.Conclusion Compared with the tomato pomace and pumpkin waste silage, treatments E and E + LMI had lower acetic and butyric acid contents. During aerobic exposure, tomato pomace and pumpkin waste had the lowest pH changes in silage. Generally, applying a combination of E and LAB inoculants improved both fermentation quality and aerobic stability of silage.